Anticancer effects of dietary administration of secoisolariciresinol diglucoside in a patient of gastrointestinal stromal tumor: a case report. Issue 6 (20th December 2020) - Wu, Hao; Wang, Yao; Chen, Jia-Tao; Wang, Li-Ping; Liu, Gui-Rong; Liu, Shu-Lin
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Gastrointestinal stromal tumor (GIST) is among the leading malignancies of the digestive system. GIST is not susceptible to chemotherapies and is prone to recurrence or metastasis after surgical operation. Secoisolariciresinol diglucoside (SDG) was suggested to have potential anticancer effects, but no clinical evidence had been available. Here we report successful treatment of a postoperative GIST case with dietary SDG. Presentation of Case: The patient was a 58-year-old man. He had GIST and received resection of small intestinal lesions 1 year before. He was diagnosed with postoperation of GIST and presented with high level of serum carbohydrate antigen 72-4 (CA72-4). The patient was then treated with dietary administration of SDG with his voluntary acceptance for 5 months, and underwent 2 serum CA72-4 measurements during this period. CA72-4 level of the patient was restored to normal range after treatment with dietary SDG for 1 month. There was no aberrant CA72-4 level, recurrence or metastasis after the treatment with dietary SDG. Discussion: This is to our knowledge the first report on application of dietary SDG on a postoperative GIST patient with aberrant level of serum CA72-4. SDG can be transformed into active substances with antitumor effects by human gut bacteria. Dietary SDG might inhibit tumorigenicity and malignant behavior of GIST cells. Conclusion: The excellent effects suggest dietary SDG to be a potential therapy for GIST, especially against recurrence or metastasis.